Novel Bifunctional Single-Chain Variable Antibody Fragments to Enhance Virolysis by Complement: Generation and Proof-of-Concept. (12th January 2014) - Huber, Georg; Bánki, Zoltán; Kunert, Renate; Stoiber, Heribert
Abstract : When bound to the envelope of viruses, factor H (FH), a soluble regulator of complement activation, contributes to the protection against a potent immune defense mechanism, the complement-mediated lysis (CML). Thus, removing FH from the surface renders viruses, such as HIV, susceptible to CML. For a proof of concept, we developed a construct consisting of recombinant bifunctional single-chain variable fragment (scFv) based on a monoclonal antibody against Friend murine leukemia virus (F-MuLV) envelope protein gp70, which was coupled to specific binding domains (short consensus repeats 19-20; SCR1920) of FH. We used Pichia pastoris as expression system in common shake flasks and optimized expression in high density bench top fermentation. Specific binding of recombinant scFv was proven by flow cytometry. The recombinant scFv-SCR significantly enhanced CML of F-MuLV in vitro implying that FH binding to the viral surface was impaired by the scFv-SCR. This novel concept to enhance virolysis may provide a new approach for antiviral treatment.